BUILDING A STRONG BRAND THROUGH AN EFFECTIVE BRANDING STRATEGY - Ismail Razak (Sean Institute, 2023)
A strong brand has a positive impact on customer perception, loyalty and a company's market share. This research will analyze marketing strategies through branding strategies that have proven successful in creating, managing and strengthening brands. This research uses a qualitative approach through descriptive methods. The research results show that building a strong brand involves a number of key strategies. Implementing an easy-to-understand logo, instilling value in the product, innovation, market research and competitor monitoring are important factors. Identifying brand barriers helps companies to improve their image and understand customer needs. A good positioning strategy plays a central role in creating brand uniqueness in the minds of consumers. Apart from that, creating a website is a modern element that supports brand visibility and interaction with customers online. By combining these approaches, companies can build a strong brand, expand market reach, and maintain competitiveness in a dynamic marketplace.